Treatment of superficial second-degree burns with a nanofiber tissue matrix: A case report - John Clayton Rodriguez; Andy H. Chen; David E. Carney (Elsevier, 2022)
Burn wound management has continued to evolve with advances in the understanding of wound healing. Treatment of partial-thickness burns consists of a wide variety of dressings and biosynthetic skin substitutes all with the goal of providing wound coverage while promoting healing. In this paper, we describe the successful treatment of a 6% total body surface area superficial second-degree thermal burn with the application of a novel fully synthetic nanofiber matrix.